Caracterização molecular de papilomavírus humano (HPV) e vírus adeno-associado (AAV) em lesões intraepiteliais de colo uterino : um estudo de seguimento - Freitas, Luciana Bueno de (2014)
The cervical cancer (CC) is one of the most frequent types of cancer in women worldwide, not only in incidence but also in mortality, with HPV as the etiological agent. Some HPV genotypes, termed high-risk (HR-HPV) and its gene variants are more associated with the induction of malignancy in the cervix, being HPV16 and 18 the most frequent types. Some infections of the genital tract may act as cofactor of carcinogenic progression of CC, but adeno-associated virus (AAV) infection seems to be inversely related, which may reflect a protective role in the development of HPV-induced cervical cancer. Therefore, this study aimed to investigate the role of AAV-HPV mixed infection and oncogenic variants of HPV in the progression of cervical intraepithelial and to follow the viral persistence / clearance and the relation to the progression / regression of cervical lesions. Cytological examinations were performed on cervical samples, collected in two moments, of women referred to the University Hospital Cassiano Antonio Moraes – HUCAM, and all of them received treatment as recommended. DNA was extracted using QIAamp® DNA Mini Kit commercial kit, following manufacturer's instructions. AAV DNA was investigated by PCR and nPCR and HPV by PCR and Hybrid Capture® (CH). AAV and HPV genotyping were performed by RFLP and RLB, respectively. From all the cases referred to the colposcopy clinic, 57.3% had normal cytology, 23.1% low grade intraepithelial lesions and 19.6% high-grade intraepithelial lesions. Out of the normal groups, 78% remained normal, while 22% progressed to lesion; from the cases with low-grade lesion, 74% regressed to normal cytology, while 78.6% of the cases with high-grade lesion showed low-grade lesion or normal cytology in the second collection. Fifty six percent and 36.5% of the samples were positive for HPV in the first and second samples, respectively. A good correlation (kappa = 0.66) between CH and PCR tests for HPV detection was observed. HR-HPV was detected in about 90% of the samples from both collections, the most common types were HPV16, 58, 51, 52 and 53. Non-European variants were associated with the development of high-grade cervical lesions, while AAV presence was inversely related to the progression of HPV-induced cervical lesions.